L’empreinte du calque - Paolo Bellomo (Itinéraires)
This article explores a translation procedure known as calque or loan translation, a type of text that emerged in comparative linguistics and stylistics at the end of the nineteenth century. First, it shows that the original term calque was in fact connected to the fine arts. It then goes on to analyze the imaginaries which are inherent to a loan translation. The main objective is to highlight the material relationship that developed between original texts and loan translations. By examining the acceptability and unacceptability of different loan words in the target language, Chateaubriand’s discourse on the calque à la vitre, and the etymology of the word calque, our intent is to study the similarities between original texts and their translations.